LITHUANIAN EMIGRANTS’ SATISFACTION WITH THEIR HOLIDAY IN HOMELAND - Viktorija Grigaliūnaitė; Lina Pilelienė (Economic Review)
Contemporary global environment leads to a situation when citizens of many countries emigrate to search for better carriers, education, or life opportunities. However, a relationship with the homeland and the families left is often kept even after settlement abroad. To maintain a bond with their native country, emigrants provide monetary transfers to their families or relatives left; invest in properties or real estate in their parent country; and return to spend their holidays in places where they grew up and spent parts of their lives. The refore, emigrants can be considered as a powerful market segment. The purpose of this paper is to determine the factors that affect emigrants’ satisfaction with the holiday in Lithuania as their native country. In order to reach the aim, a questionnaire survey was distributed to 229 emigrants spending their holiday in Lithuania. Based on the respondents’ answers, the factors affecting emigrants’ satisfaction with their holiday in Lithuania were determined. The results enabled establishing two variables that have a direct effect on Lithuanian emigrant satisfaction: accommodation and catering and environmental preservation. However, considering loyalty, different factors were found as being significant. Emigrant loyalty to spending holiday in their homeland Lithuania can be encouraged directly through satisfaction, or by enhancing accommodation and catering and activities in destination. The factors ‘natural features of the destination’; ‘destination aesthetics’; and ‘destination marketing’ were found to be non-significant; they did not affect Lithuanian emigrants’ satisfaction or loyalty to a destination. Knowing the determined factors that affect emigrants’ satisfaction with the holiday in Lithuania as their native country will enable practitioners to allocate their investments in a way leading to better satisfaction of emigrants’ needs, which in turn would attract a significant and constantly growing market segment. Tourist satisfaction, its determinants and consequences are highly influenced by the context of tourism, tourist purposes, and tourist nationality. The empirical findings in this study provide a new understanding of tourist satisfaction considering emigrants as tourists in their motherland.